HARNESSING RESOURCE RENTS FOR DEBT REDUCTION: A STUDY OF OIL-RICH SUB-SAHARAN AFRICAN COUNTRIES - Akinsola, Motunrayo O.; Akinsola, Foluso A.; Iwegbu, Onyebuchi (Economic Annals, 2025)
This paper examines the effect of oil resource rents and economic complexity on the debt burden of five oil-rich Sub-Saharan African countries between 1995 and 2019. A panel autoregressive distributed lag estimation technique was used to estimate the models; the results reveal a negative and significant impact of economic complexity and natural resources rents on debt services of the selected oil-rich African countries. The paper also shows that using natural resources rents to enhance the complexity of the economy reduces public debt burdens. The implication is that greater economic complexity and natural resources rents may reduce the tendency of oil-rich countries to experience debt crises in the long run. The paper recommends that a greater deployment of natural resources rents for productive purposes may create a conducive investment climate, reducing the incidence of debt. Finally, policy makers in these economies should take advantage of natural resources rents to diversify their economies in order to deepen economic complexity and reduce the burden of public debt.